2019
DOI: 10.1002/cctc.201901744
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of SnO2 Support in Water‐Tolerant Methane Combustion: In situ Observation of Pd(OH)2 and Comparison with Pd/Al2O3

Abstract: Quantitative analysis of poisonous Pd hydroxide phase formation during methane combustion in the presence of water is performed via in situ X‐ray absorption spectroscopy from 200 to 500 deg C for palladium catalysts supported on tin and aluminum oxides. Water presence inhibits oxidation of the metallic Pd; for the Pd/Al2O3 catalyst the major oxidation product is Pd(OH)2, with PdO being the dominant phase on the Pd/SnO2 system. Tin dioxide is reduced during methane oxidation in the presence of water, regardless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 57 publications
(132 reference statements)
1
19
0
Order By: Relevance
“…For this model adaptation, thermodynamic consistency is still guaranteed, because the microkinetic mechanism remains uniform, which is the main advantage of the chosen method. Whether the active particles react to the gaseous environment with a different active facet or shape, i.e., as observed for Zn-O-Cu catalysts for methanol synthesis [30][31][32], or in combination with hydroxyl formation [33], solely a change in F cat,geo accounts for a different catalytic activity.…”
Section: Modeling the Water Inhibition Effectmentioning
confidence: 99%
“…For this model adaptation, thermodynamic consistency is still guaranteed, because the microkinetic mechanism remains uniform, which is the main advantage of the chosen method. Whether the active particles react to the gaseous environment with a different active facet or shape, i.e., as observed for Zn-O-Cu catalysts for methanol synthesis [30][31][32], or in combination with hydroxyl formation [33], solely a change in F cat,geo accounts for a different catalytic activity.…”
Section: Modeling the Water Inhibition Effectmentioning
confidence: 99%
“…So far, there have been different interpretations of the inhibitory effects of water on methane oxidation, and a clear explanation of it is still missing 6,10,[24][25][26] . It was initially reported that the formation of stable and inactive surface hydroxide, Pd(OH) 2 , inhibited and deactivated supported palladium catalysts 8,12 27 . They also showed that water inhibits the oxidation of metallic palladium, which is supported by temperature programmed oxidation (TPO) experiments 28 and electron microscopy 29 .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the known inhibitory effect of water on the steady-state, lean methane oxidation activity 46,52,95 of a commercial 3%Pd/Al2O3 monolith catalyst, has been axially profiled using the SpaciMS technique. The resulting reaction profiles have been utilised in screening a number of hypothesised global kinetic models via a built in parameter estimation routine developed using Athena Visual Studios, coupled with a 1D heterogeneous single channel model.…”
Section: Introductionmentioning
confidence: 99%